AB0215 Significance of Relationship between Anti-Tif1 Autoantibodies Profiles and Cancer-Associated Myositis. (10th June 2014) - Lu, X.; Yang, H.; Yuan, K.; Peng, Q.; Wang, G.
Abstract : Background: Idiopathic inflammatory myositis (IIM) are a group of heterogeneous autoimmune diseases that mainly affect skeletal muscle. A number of studies have indicated the significant relationship between IIM and malignancy. Myositis-specific anti-P155/140 autoantibodies has been identified as one of the strongest risk factors of developing cancer-associated myositis (CAM). Recent reports have demonstrated anti-P155/140 autoantibodies can recognize the antigens of transcription intermediary factor (TIF)-1 family proteins including TIF-1α, TIF-1β and TIF-1γ. However, it is not clear whether the anti-TIF1 autoantibodies profiles are associated with CAM. Objectives: To study the relationship between anti-TIF1 autoantibodies profiles and cancer-associated myositis (CAM) and to define the diagnostic value of different subtypes of anti-TIF1 aotuantibodies for CAM. Methods: Sera from 156 with dermatomyositis (DM), 55 with polymyositis (PM), 70 with systemic lupus erythematosus (SLE), 60 with rheumatoid arthritis (RA), 46 with primary Sjogren syndrome (PSS), 14 with systemic sclerosis (SSc), 49 with kinds of malignancies (including 21 with lung cancer, 16 with breast cancer, 8 with colon cancer and 4 with non-Hodgkin lymphoma) and 40 healthy controls were examined by immunoprecipitation assays followed by western blotting. Results: In summary, 32 of 156 sera from patients with DM (20.5%) were positive for at least one anti-TIF1 autoantibodies. There are four subtypes of anti-TIF1 autoantibodies profiles existed in patients with DM including only anti-TIF-1α-positive (12.5%), only anti-TIF-1γ-positive (62.5%), both anti-TIF-1α and anti-TIF-1γ-positive (21.9%) and both anti-TIF-1β and anti-TIF-1γ-positive (3.1%). However, only anti-TIF-1α-positive (7.3%) was observed in patients with PM. No patients with other CTDs as well as malignancies and healthy controls were positive for these autoantibodies. The sensitivity and specificity of presence of anti-TIF-1α antibodies for the diagnosis of CAM were 42.9% and 96.5%, respectively and those of anti-TIF-1β antibodies were 0% and 99.3%, respectively and those of anti-TIF-1γ antibodies were 64.3% and 86.6%, respectively. Application of areas of ROC curves to identify the best performance of test of anti-TIF1 autoantibodies profiles were 0.70, 0.50, 0.76, 0.74 and 0.71, respectively. The incidence of CAM in both anti-TIF-1α and anti-TIF-1γ-positive patients compared to the only anti-TIF-1α-positive group and only anti-TIF-1γ-positive group was statistically increased (p<0.05). Conclusions: Anti-TIF1 autoantibodies profiles can exist in adult patients with PM and DM and could be specific serum markers for CAM. Joint detection of anti-TIF1 autoantibodies profiles can improve the diagnostic capacities for CAM. References: Zampieri S, Valente M, Adami N, Biral D, Ghirardello A, Rampudda ME, et al. Polymyositis, dermatomyositis and malignancy: a further intriguing link. Autoimmun Rev. 2010; 9(6): 449-53. Fujimoto M, Hamaguchi Y, Kaji K, Matsushita T, Ichimura Y, Kodera M, et al. Myositis-specific anti-155/140 autoantibodies target transcription intermediary factor 1 family proteins. Arthritis Rheum. 2012; 64(2): 513-22. Targoff IN, Mamyrova G, Trieu EP, Perurena O, Koneru B, O'Hanlon TP, et al. A novel autoantibody to a 155-kd protein is associated with dermatomyositis. Arthritis Rheum. 2006; 54(11): 3682-9. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.2390